KOLABORASI KOMISI PEMILIHAN UMUM DAN BADAN KESATUAN BANGSA DAN POLITIK DALAM MENDORONG PARTISIPASI MASYARAKAT PADA PELAKSANAAN PEMILIHAN KEPALA DAERAH SERENTAK 2024 DI KOTA BANJAR - Daryatno, Achmad; Roufurohim, Roufurohim (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study aims to examine the collaboration between the General Election Commission (KPU) and Kesatuan Bangsa Politik (Kesbangpol) of Banjar City in encouraging citizen participation in the 2024 Simultaneous Regional Elections. The research method applied is qualitative, with data collection through in-depth interviews with selected informants, document studies, and other supporting sources. Informants were selected using purposive sampling techniques, while data analysis used descriptive methods. The findings reveal that the cooperation between the KPU and Kesabngpol has fulfilled all indicators in the theory of collaboration. This collaboration began with both parties' awareness of the importance of increasing voter participation. Although the institutional structure that was built was informal, the division of tasks between institutions was clear. The leadership style applied emphasizes transparency and active communication, while the collaboration process is realized through open discussions, increased trust, mutual agreements, and collective understanding. Factors supporting the success of the collaboration include effective communication, support from local leaders, and alignment of organizational goals. On the other hand, obstacles such as limited budgets, lack of official records, and low public political awareness also influenced the process. The research concluded that the synergy between the KPU and Kesbangpol in Banjar City was effective in boosting public participation, although it still needs to be strengthened through institutional mechanism improvements and more adequate resource allocation.